The determinants of financial distress cost: A case of emerging market - Muhammad Farooq; Ahmed Imran Hunjra; Saif Ullah; Mamdouh Abdulaziz Saleh Al-Faryan (Cogent Economics & Finance, 2023)
This study analyses the cost of financial distress of non-financial firms listed on the Pakistan stock exchange. Furthermore, it considers the moderating role of concentrated ownership in the relationship between debt and expected financial distress costs. We used the panel data of 214 firms from 2010 to 2018 to analyse the results. We apply fixed effect model to test the hypotheses. We find that ex-ante financial distress costs are based not only on the probability of financial distress but also affect the amount of time and money spent during the distress period. The use of tangible fixed assets and long-term leverage lowers the cost of financial distress, whereas the use of short-term debt has no significant impact on the cost of financial distress. Furthermore, the company's ownership structure dampens the impact of these factors. Corporate management may reduce the cost of financial distress through better management of fixed assets and financial leverage.
Keywords: G32; M41; 330; collateral; financial distress cost; financial distress likelihood; interest coverage ratio